MENINGKATKAN MUTU UMAT MELALUI PEMAHAMAN YANG BENAR TERHADAP SIMBOL ACINTYA (PERSPEKTIF SIWA SIDDHANTA) - Widya Sena, I Gusti Made (Jurnal Penjaminan Mutu, 2016)
God is very difficult to understand with eyes. In order to know God, His nature, and His personification, use of various symbols can be helpful, which suggests the unification of two elements, namely the physical and spiritual ones. Acintya is the symbol or manifestation of God 's Omnipotence. It is the â€œunimaginableâ€ that turns to be the â€œimaginable" through potraits, reliefs, or statues. All of these symbols are manifestation of the Acintya that takes the form of the dance of Shiva Nataraja, as the depiction of the Omnipotence of God, to bring in the actual symbol of the "Unthinkable " that have a meaning that people are in a situation where emotions religinya very close with God.